Creating White Australia. - Carey, Jane. (Sydney University Press, 2009)
The adoption of White Australia as government policy in 1901 demonstrates that whiteness was crucial to the ways in which the new nation of Australia was constituted. And yet, historians have largely overlooked whiteness in their studies of Australia's racial past. Creating White Australia takes a fresh approach to the question of 'race' in Australian history.